LATIHAN KEWIRAUSAHAAN DAN WIRAUSAHAAN BERJAYA : KAJIAN DI KOTA MAKASSAR SULAWESI SELATAN - Rijal, Muhammad (JPP (Jurnal Politik Profetik), 2016)
Enculturalization of entrepreneurship is an increasingly important element toovercome unemployment and poverty reduction. The Department of Labor and Transmigration of South Sulawesi have been conducting entrepreneurship training programs since 2001 known as Tenaga Kerja Mandiri (TKM) and Kelompok Usaha Mandiri (KUM). This article focuses on the extent of such a program and its’ability to produce successful entrepreneurs by assessing the impact of training that has been carried out. This thesis is based on entrepreneurial behavioral theory, achievement motivation theory, planned behavior theory, CIPP model, entrepreneur development model, entrepreneurship training performance model (E/P) and entrepreneurship education model (E/E). This the study was conducted among 217 entrepreneurs from Makassar City, who had graduated from entrepreneurship training in 2001. The instrument uses aquestionnaires include entrepreneurial success indicators, motivation, and training components. Descriptive analysis is used to classify the participant’s business profile and the entrepreneurship programs. Multiple regression analysis is used to determine the entrepreneurial success factors. The findings indicate that 94% of the participants have become successful entrepreneurs, while 6% have been unable to sustain their business. Overall, the study reveals that successful entrepreneurs are influenced by motivation, and fitness of the training topics, teaching ability, infrastructure, and the ability to master the content of entrepreneurship. A lack of sufficient capital is identified as a key factor in the failure of a business, followed by entrepreneurship knowledge, and educational level. Thus, sufficient funding and selection of appropriate participants could improve the effectiveness of this entrepreneurial program.